Spontaneous scalarization - Doneva, Daniela D.; Ramazanoǧlu, Fethi M.; Silva, Hector O.; Sotiriou, Thomas P.; Yazadjiev, Stoytcho S. (Reviews of Modern Physics, 2024)
Scalarization is a mechanism that endows strongly self-gravitating bodies, such as neutron stars and black holes, with a scalar-field configuration. It resembles a phase transition in that the scalar configuration appears only when a certain quantity that characterizes the compact object, for example, its compactness or spin, is beyond a threshold. A critical and comprehensive review of scalarization, including the mechanism itself, theories that exhibit it, its manifestation in neutron stars, black holes and their binaries, potential extension to other fields, and a thorough discussion of future perspectives, is provided.
Keywords: General Physics and Astronomy